PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KEARIFAN LOKAL MATA PELAJARAN IPS KELAS IV SDN 161 PEKANBARU - Vebrianti, Yossy; Noviana, Eddy; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study is the development of student worksheet based on local wisdom that is designed to integrate various forms of local wisdom into social studies to introduce the values of local wisdom in the local area. worksheet developed using 4-D model of which consists of four phases: define, design, develop, and disseminate. The instrument used is the validation of a questionnaire, pretest and posttest questionnaire on student responses. Worksheet has been designed validated by experts IPS SD material, media, language, and a fourth-grade teacher. After generating a worksheet that has been validated then tested in grade IV SDN 161 Pekanbaru. The results showed that the worksheet based on local wisdom made by researchers stated very decent validator with a score of 88.3 percent. In the pilot phase is limited, obtained an average score of 45.30 pretest and posttest at 63.33. For N-Gain on the pretest and posttest was 0.33, with the medium category. Worksheet student responses based on local knowledge made by researchers stated very well with a percentage score of 95.76. At this stage of deployment (deploy) products in elicits responses IVA class 82.42 and at 88.91 IVC classes with very good category. For the teacher's response gained an average of 90.1 categorized as very feasible.Key Words: Development, Worksheet, Local Wisdom